(untitled) (IAHS Medical Journal, 2024)
Background: In the contemporary context, helicopter parenting which is a common practice and in Southeast Asia region, it is a growing parenting approach. It has several components that affect adolescents and emerging adults physical, psychological and social well-being. The aim of the study is to measures the parenting style for the adolescent for which the Helicopter Parenting Scale (HPS) was used. Material and methods: A cross-sectional study was conducted to assess the state of helicopter parenting style of parents on late adolescents of Police Lines School and College, Rangpur, Bangladesh. Results: The mean age of the adolescent was 17.7±0.6 years. The mean of HP scores was 3.6±0.5. About three out of five participants had a perceived average level of HP (58.9%) and a few of them had a high level of HP (2.3%). A statistically significant association found within the level of HP and adolescent’s family type (p<0.05) and the perceived level of HP was average among the adolescents who came from the nuclear family (61.8%). The HP scores were high in the nuclear family (3.62±0.413) and parents’ living together (3.59±0.422). There were significant differences found in the HP scores with the adolescent’s family type and their parent’s relationship state (p<0.05). Conclusion: The study found that nuclear families were more likely to adopt helicopter parenting than other types of families, with their perceived level of this parenting style being assessed as averagely good. IAHS Medical Journal Vol 7(1), June 2024; 26-31